(3GdTaG HJYQja Mbhb GdeUWais - (3GdjMUHj, CHh GdaVd, GdbGVj YjGV, YjGV Hf ehSi Hf YjGV, J(B544(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdefaQO HGSeg GdCSeiCeG HYO CTQb Gddg bdHj hbdHc HCfhGQ Gdjbjf aEfc cQQJ GdSDGd aj eLehY jJVef GdJYQja HbOQ GdeUWai Ydjg GdSdGe heG jLH dg ef JhbjQ hEcQGe heG Mce ef de jha hGLH YXje Pdc GdbOQaEf GdcdGe aj Pdc jSJOYj JbQjQ CUhd hJMQjQ aUhd, hdeG fhjJ JbQjHg hOQL JHhjHg JQLeJg HGdTaG HJYQja Mbhb GdeUWai Udi Gddg Ydjg hSdes
(3BNQgG (B:s
(3hbGd CHh YeQGf aj QLd bGd dh TgO Ydj CHh HcQ GdUOjb Cfg Ef cGf aj eKd eG jLhR ajg GdTGgO GdhGMO adG TjA Ydjg hGf cGf CQGO ZjQ gPG ajVQH VQHG jHdZ Hg MO GdehJ hPcQhgG QhGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 5 / 99s
(3eYLe GdeDdajf(B: 2 / 588s
(3cTa GdXfhf(B: 2 / 1052s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJGQjNs